Automatic Temperature Detection and Sanitization with Authorized Entry using Face Mask Detection - Rahman, Rukia (Journal of Electronics and Informatics, 2022)
To contain the chain of Covid-19, taking on the role of Engineering Ambassador of humanity in these dire conditions, this paper develops an electronic equipment referred holistically as “Covid Tunnel” or “Disinfectant Tunnel”. The general thesis from which the whole work has evolved is to make use of temperature control and automation by programming to try to pin the potential host of virus in possible hotspots viz., hospitals, administrative complexes, strategic junctions, etc. The first and foremost import of this benevolent project is the application of Automatic Temperature Control. Arduino Nano Temperature Control is employed for checking the temperature of each entrant at the entrance gate. For instance, if a person entering happens to have a body temperature above 38C, the buzzer goes on indicating a red flag for the entry. The second and equally important process is filtering based on the face mask. Now, a webcam attached right after, which is program-based on Python, Open CV, Tensor Flow etc. provides the necessary input and the program searches for the face mask. If the entrant is unmasked, a voice in Urdu commands for wearing of the face mask. While a masked person enters, the automated sanitizer pops out for sanitizing as a precautionary measure. The sanitizer itself is automated by a DC motor which in turn is driven by MOSFET integrated circuit. Thusly, this paper tries to kick in with the Electronics and Information Technology and helps arrest the spread of the virus in the community, anticipating a Coronavirus-free world.